Differential remineralization of major and trace elements in sinking diatoms. (7th April 2014) - Twining, Benjamin S.; Nodder, Scott D.; King, Andrew L.; Hutchins, David A.; LeCleir, Gary R.; DeBruyn, Jennifer M.; Maas, Elizabeth W.; Vogt, Stefan; Wilhelm, Steven W.; Boyd, Philip W.
Abstract : Macronutrients in sinking phytoplankton are typically remineralized at different rates, but less is known about the fate of micronutrient metals associated with sinking cells. Scavenging, the presence of co‐occurring abiotic particles, and inadvertent contamination limit the utility of bulk analytical approaches to study remineralization of trace metals in sinking phytoplankton. We used synchrotron x‐ray fluorescence mapping to measure macronutrients (P, S, and Si) and trace metals (Fe, Ni, and Zn) in individual cells of the diatom Asterionellopsis glacialis during a spring bloom in subtropical waters off New Zealand. P, S, Zn, and Ni were released significantly faster than Fe and Si from sinking cells in the upper 200 m. Bulk particulate element fluxes to sediment traps indicated similar trends, but biogenic silica flux was attenuated much faster than Si was lost from intact sinking cells collected in the traps. The metals were spatially co‐located with P and S in upper ocean cells, but this association with P and S (based on a spatial resolution of 450 nm) was largely absent in sinking cells. In contrast, Fe retained a weak spatial association with Si, suggesting that remineralized Fe may be re‐scavenged onto cell surfaces. As a result, dissolved Fe : macronutrient stoichiometries in the water column likely underestimate stoichiometries in sinking cells. We propose linkages between the selective loss of diatom cellular components (e.g., ribosomes or phospholipid membranes, Zn‐finger proteins, and urease) and the observed recycling of specific elements (P, Zn, and Ni, respectively), which set the stoichiometry of macro‐ and micronutrient supply to surface waters.